Evaluation Of Passenger Services At Kendari France Port Based On The Regulation Of The Minister Of Transportation Number Pm 39 Year 2015 Southeast Sulawesi Province - Paulina M Latuheru; Siti Nurlaili Triwahyuni; Reka Linda Yani (IWTJ : International Water Transport Journal, 2022)
The Kendari crossing harbor is a pioneer crossing that serves the three-hour commuter crossing. The government has made every effort to support economic development in the konave region. The level of services felt by those who use services may have a bearing on whether or not they should be carried out in the harbor, especially those felt at the harbor that must meet passenger service standards because they are consumers that determine the growth or failure of transportation systems. The method used to analyze existing problems is a minimum standard of compliance analysis with existing conditions. According to the corresponding treaty, the corresponding value of each passenger service requirement is 4, and the corresponding value of each passenger service requirement is 14 and 18 is also available. Based on the analysis, the conclusion is that there is still less service of several transit transit routes such as the waiting room, the toilets, evacuation route instructions, evacuation point point, the musholah facility. Inadequate, no passenger baggage service, no advanced transit information, information of shipwrecks and no masth has not met the standard requirements of passenger service in the port.